2014
DOI: 10.1096/fj.14-256495
|View full text |Cite
|
Sign up to set email alerts
|

Sperm‐derived WW domain‐binding protein, PAWP, elicits calcium oscillations and oocyte activation in humans and mice

Abstract: Mammalian zygotic development is initiated by sperm-mediated intracellular calcium oscillations, followed by activation of metaphase II-arrested oocytes. Sperm postacrosomal WW binding protein (PAWP) fulfils the criteria set for an oocyte-activating factor by inducing oocyte activation and being stored in the perinuclear theca, the sperm compartment whose content is first released into oocyte cytoplasm during fertilization. However, proof that PAWP initiates mammalian zygotic development relies on demonstratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
113
2
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(121 citation statements)
references
References 40 publications
4
113
2
2
Order By: Relevance
“…Among these factors, PLCf has emerged as the strongest candidate and several studies have shown the correlation between absence or deficiency of PLCf with failed fertilization in globozoospermic men (Heytens et al, 2009;and Aghajanpour et al, 2011). However, a growing body of evidence has challenged the importance of PLCf as the key SOAF and proposed other candidate proteins, particularly PAWP and TR-KIT, as the major SOAFs (Muciaccia et al, 2010;Aarabi et al, 2014b;Amdani et al, 2015;Nomikos et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Among these factors, PLCf has emerged as the strongest candidate and several studies have shown the correlation between absence or deficiency of PLCf with failed fertilization in globozoospermic men (Heytens et al, 2009;and Aghajanpour et al, 2011). However, a growing body of evidence has challenged the importance of PLCf as the key SOAF and proposed other candidate proteins, particularly PAWP and TR-KIT, as the major SOAFs (Muciaccia et al, 2010;Aarabi et al, 2014b;Amdani et al, 2015;Nomikos et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…We need further systematic studies to identify the best method to activate human ROSI oocytes. Other oocyte-activating agents to be considered include: Ca 2+ ionophore (20,45,46), phosphatidyl inositol (47,48), phospholipase Cζ (49-51), 4-(diemethylamino) pyridine (52), and postacrosomal protein PAWP (53)(54)(55).…”
Section: Possible Reasons For Previous Failures Of Human Rosimentioning
confidence: 99%
“…We cannot exclude the presence and relevance for the phenotype observed of alteration in other candidate activation molecules, such as PAWP [27,28], however, due to the limited amount of patient sample available for study, we elected to focus on PLCζ.…”
Section: Icsi Failure and Plcζ Presence/distributionmentioning
confidence: 99%